The anthropology of X. Zubiri - Savignano, Armando (Medicina e Morale, 1991)
The article analyzes the thought of the Spanish philospher X. Zubiri, and in particular it studies the originality of his contribution on the anthropological level. Anthropology takes shape through a fertile interaction between philosophy and science- The conception of the consitutive essence of man makes use of the contributions of science (genetics, sociology, psychology, etc.) without reducing itself to these sectors. The stages of psychosomatic evolution intrinsecally require an ex nihilo creative act. The organism and the psyche are subsystems of the human substance, understood as a structural unit of the individual which is open to the historical dimension and to the theologal dimension. The consideration of that which is specifically human implies metaphysics and realist personalism.